Assessment of the treatment efficiency of an urban stormwater pond and its impact on the natural downstream watercourse. (15th November 2018) - Ivanovsky, A.; Belles, A.; Criquet, J.; Dumoulin, D.; Noble, P.; Alary, C.; Billon, G.
Abstract: During the last few decades, stormwater ponds have become an alternative management practice in order to avoid flooding and to contain rainwater and runoff in urban areas where impervious land cover has increased. A second purpose of stormwater ponds is to improve the quality of runoff water that is usually contaminated with nitrogen, phosphorus, metals and organic micropollutants. Processes used are based on natural methods such as settlement and contribute to minimize the impact of these inputs to the natural aquatic system. This study aims to better understand the behavior of a wet stormwater pond, Heron Lake (33 ha) located in the city of Villeneuve d'Ascq in northern France through various indicators [trace metals, PAHs, PCBs, caffeine (CAF), carbamazepine (CBZ), nutrients and pathogens]. For that purpose, water quality was monitored for 1 year, mainly at the entrance and at the outlet of the lake. Sampling have also been done in the downstream aquatic environment, the Marque River. Sediments were sampled in the lake to evaluate the pollution trapped during sedimentation. Our results of both water and sediment sampling highlight: (i) the wastewater input into the Heron Lake is estimated to be equivalent to that of roughly 3800 inhabitants; (ii) the removal rates observed at the outlet, relative to concentrations at the entrance channel, vary as follows for these dissolved species: 24% for NO3 − and PO4 3−, 28% for CBZ, 35% for Cu, 63% for Pb, 78% for CAF, 84% for Zn and up to 93% for NH4 + ; (iii) there are high levels of sediment contamination with metals, PAHs and PCBs at the entrance channel; (iv) the eutrophication of this pond is attributed to persistent high nutrient concentrations in both water and sediment, and has contributed to the development of an invasive macrophyte, the Elodea nuttallii ; and (v) there appears to be only a negligible impact of the discharge from the lake to the natural watercourse, contributing annual loads of <2 up to 6% of the total amount of Cu, Pb, Zn, CAF, CBZ and nutrients measured in the Marque River, and having a slight diluting effect on concentrations in the Marque River. Graphical abstract: Image 1 Highlights: Management processes to purify rainwater during runoff on the soils and other covers. Multiple contamination including wastewater inflows in the stormwater pond. Efficacy as a settlement pond for particulate matter. The treatment of the soluble pollution in the lake appears significant but limited.